Creating an enabling environment for agricultural innovation in emerging markets - Ires, Idil (International Water Management Institute, 2025)
Market is the structure for the development and delivery of innovations that are able to address environmental, societal, and economic challenges. The lack of enabling conditions for market development has resulted in low investment levels and economic stagnation, impacting livelihoods in Africa. Although there have been efforts to implement market-driven reforms, challenges such as inadequate policies, weak legal frameworks, transparency issues and bureaucratic inefficiencies pose significant risks for public and private investments and for their potential to reach the target beneficiaries. This situation also discourages development partners and businesses from investing in the region.Technical assistance is crucial to improve the investment climate. This paper presents a framework to help governments create a more conducive environment for agricultural market development and the private sector to navigate through the existing challenges. Traditional technical assistance practices have faced criticism for adopting a one-size-fits-all approach that overlooks local contexts. Recently, however, there has been a shift towards more context-based and adaptive assistance, which informs this framework. This framework emphasizes key elements that contribute to an enabling environment, including institutions, such as policies, regulations, and legal frameworks, as well as clear market and regulatory information that help reduce transaction costs. The framework is theoretically based on new institutional economics and political economy approaches. It focuses on assistance in three areas with three categories of delivery partners: policy support to governments, institutional capacity strengthening (especially of National Agricultural Research and Extension Systems) and (agri)business acceleration support to small- and medium-scale enterprises. Through such assistance, this framework seeks to help create an enabling environment for the delivery of innovations that offer solutions to emerging climate, societal and economic crises. These solutions, especially those developed and scaled by the private sector, are targeted toward recipients such as farmers (including women and the youth), marginalized groups, displaced communities, refugees and migrants. The framework utilizes value chain and market development as the primary delivery structures. This framework has guided several recent enabling environment assistance practices under CGIAR’s International Water Management Institute (IWMI). This paper explores these practices and positions CGIAR as a strong technical assistance partner. While this framework offers a systematic approach to analyzing the enabling environment, the technical assistance driven by this framework promotes collaboration and co-creation. It actively engages governments, national research and extension offices, farmers and other stakeholders in influencing policies and business transaction advisories that directly benefit them. Furthermore, it aims to strengthen their capacities to diagnose and overcome enabling environment challenges as they arise. By helping to create an enabling environment for the private sector—especially small- and medium-scale enterprises that innovate and scale—and derisking the investment climate, this framework seeks to strengthen agrifood market systems to foster food security and alleviate poverty.